Pengaturan Perjanjian Kawin Di Negara-Negara Berbasis Civil Law - Hariani, Widika Shepia; HS, Salim (Private Law, 2024)
The objective of this study is to examine the regulation of marital agreements within the legal systems of Indonesia, the Netherlands, China, and Germany. The research methodology employed is normative legal research with a focus on statutory, conceptual, and comparative approaches. The findings indicate that in Indonesia, marital agreements are governed by Law Number 1 of 1974 concerning Marriage, in conjunction with Constitutional Court Decision Number 69/PUU-XIII/2015, as well as the Compilation of Islamic Law. In the Netherlands, marital agreements are regulated in the Dutch Civil Code, Articles 1:114 to 1:148. In China, regulations can be found in the Chinese Civil Code, Article 1046. Meanwhile, in Germany, regulations are stipulated in the German Civil Code, Articles 1415 to 1449.